A landscape laboratory in Germany : reaching out for new landscape concepts - Hamm, Astrid (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
The highly industrialised "Ruhr" region in north-western Germany has undergone considerate structural changes over the past four decades, as industrialisation has seized and left the region with major challenges for its regional development in terms of urban planning, as well as social, economic, and environmental aspects. As many heavy industries, such as coal and steel mining, have moved away, they have left vast amounts of "useless" industrial land behind. New land use concepts have to be developed for some of this land that cannot be used for urban development (housing, industries). Biomass production has become an important source of renewable energy for the future. However, its potential has not been fully exploited in Germany, and more research is required, especially in terms of woody biomass production (energy forests). As recreation connected with nature has become an important factor in a highly urbanised area like "Ruhr", this report investigates the possibility of linking energy forests with recreational urban forests on post-industrial land in Germany's "Ruhr" region, using the conceptual framework of a landscape laboratory as a tool to combine and implement these different concepts. Furthermore, it presents a concept for a German landscape laboratory where biomass production can be implemented as part of a recreational landscape.